2018
DOI: 10.18632/oncotarget.25263
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacokinetics of DS-6051b in Japanese patients with non-small cell lung cancer harboring ROS1 fusions: a phase I study

Abstract: Oncogenic ROS1 and NTRK fusions were reported in solid tumors, including non-small cell lung cancer (NSCLC). DS-6051b is an oral, potent selective small molecule tyrosine kinase inhibitor. We report the safety, tolerability, efficacy, and pharmacokinetics of DS-6051b in 15 Japanese patients with NSCLC harboring ROS1 fusions. Patients received DS-6051b once daily (400 mg n = 6; 600 mg n = 6; or 800 mg n = 3) for cycles of 3 weeks. Safety, tolerability, maximum-tolerated dose, pharmacokinetics, and recommended d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…A smaller phase I study in Japan that enrolled 15 patients with ROS1 þ NSCLC concluded that the MTD and recommended phase II dose for taletrectinib was 600 mg once daily (17). Two grade 3 ALT elevations were observed at the 800-mg once-daily dose and were considered as DLTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller phase I study in Japan that enrolled 15 patients with ROS1 þ NSCLC concluded that the MTD and recommended phase II dose for taletrectinib was 600 mg once daily (17). Two grade 3 ALT elevations were observed at the 800-mg once-daily dose and were considered as DLTs.…”
Section: Discussionmentioning
confidence: 99%
“…Among the total of 15 patients with ROS1 þ NSCLC enrolled, ORR was 66.7% for the nine evaluable patients who were crizotinib-na€ ve and 33.3% for the three patients with evaluable crizotinib-refractory ROS1 þ . Activity against CNS metastasis was also observed (17). There was no patient with NTRK fusion-positive tumors or NET enrolled in the Japanese phase I trial (17).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the cohort of 12 patients with ROS1 -rearranged tumors and including seven crizotinib pretreated patients, an objective response was achieved by 6 (50%) (14). Clinical activity seen with other TKIs in ROS1 -rearranged NSCLC has also been described (Tables 1,2), (15,16). …”
mentioning
confidence: 84%
“…12 Responses to cabozantinib, lorlatinib, DS-6051b and repotrectinib were indeed observed, with a special mention to the last drug, retaining significant activity against brain disease and, even more remarkably, against the recalcitrant ROS1 G2032R mutation. 11,12,14,15,17,19 The evidence concerning the activity of each mentioned ROS1-TKI against specific ROS1 mutants will be likely extended, given the current documentation of resistance mutations from ctDNA in ROS1-positive NSCLC patients, 39,40 similar to EGFR-mutated and ALK-rearranged ones. 41,42 The largescale availability of such analyses, bypassing the practical issues of tumor biopsies, would allow the systemic capture of resistance mechanisms to ROS1 inhibitors and pave the way for the following correlations with drug activity.…”
Section: Entrectinib Toxicity Spectrummentioning
confidence: 99%
“…Besides crizotinib (the only drug approved by both FDA and EMA for ROS1-driven NSCLC), additional TKI have shown activity and efficacy in ROS1-rearranged lung cancer: ceritinib, cabozantinib, entrectinib, lorlatinib, brigatinib, DS-6051b and repotrectinib ( Figure 1). [10][11][12][13][14][15][16][17][18][19] According to NCCN guidelines, lorlatinib is the only ROS1-TKI approved after crizotinib failure, 20 based on available clinical trial data. 14,15 Similarly to what observed in EGFR-and ALK-positive diseases, the novel TKI can contribute to the prolongation of disease control (turning out to be a surrogate of OS) in two alternative ways.…”
Section: Introductionmentioning
confidence: 99%